Histochemistry - Zhou, Jinsong, 1970-; Xi'an Jiaotong University Press Co. (Berlin ; Boston : De Gruyter, 2017)
This book systematically illustrates theories and technologies in Histochemistry, including different kinds of enzymes, immunohistochemistry, polymerase chain reaction, related electron microscopic cytochemical techniques as well as the quantitative assay metrology. Abundant experiments as well as vivid images are demonstrated, making the book an essential reference for both graduate students and researchers in biochemistry.
Frontmatter -- Preface -- Acknowledgments -- Contents -- Contributing authors -- 1. Introduction -- 2. Tissue preparation -- 3. Carbohydrate and its derivatives in histochemistry -- 4. Nucleic acid histochemistry -- 5. Lipid histochemistry -- 6. Enzyme histochemistry -- 7. Basic theory of immunohistochemistry -- 8. Commonly used methods in immunohistochemistry -- 9. Specificity and sensitivity of immunohistochemistry -- 10. Double-staining immunohistochemistry technology -- 11. Lectin histochemistry -- 12. Progresses of in situ display -- 13. In situ hybridization histochemistry technology -- 14. In situ polymerase chain reaction histochemical technology -- 15. Electron microscopic histochemistry technology -- 16. Quantitative assay of histochemistry experiment results -- Recommended readings -- Appendix 1. Commonly used buffer in histochemistry -- Appendix 2. Histochemistry and immunohistochemistry experiments -- Index.
Print version record.
Includes bibliographical references and index.
In English.
Online resource; title from PDF title page (publisher's Web site, viewed 13. Sep 2017).
eBooks on EBSCOhost
Keywords: Histochemistry; Diagnostic immunohistochemistry; Histocytochemistry -- methods; Immunohistochemistry -- methods; Biochemical Phenomena; Histocytochemistry; Histochimie; Immunocytochimie clinique; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Diagnostic immunohistochemistry; Histochemistry; Histochemie; (Produktform)Electronic book text; (Zielgruppe)Fachhochschul-/Hochschulausbildung; (BISAC Subject Heading)SCI010000; (BISAC Subject Heading)SCI013020: SCI013020 SCIENCE / Chemistry / Clinical; (BISAC Subject Heading)SCI007000: SCI007000 SCIENCE / Life Sciences / Biochemistry; TB: Textbook; (VLB-WN)9675; (Produktrabattgruppe)PN: nicht rabattbeschränkt/Sortimentstitel